Freestanding 3d Graphene-Nickel Encapsulated Nitrogen-Rich Aligned Bamboo Like Carbon Nanotubes for High-Performance Supercapacitors with Robust Cycle Stability - Singh, D (Wiley-VCH Verlag, 2015)
3D hierarchical structures are reported based on graphene-nickel encapsulated nitrogen-rich aligned bamboo like carbon nanotubes, which show not only high-performance supercapacitance behavior but also a great robust cyclic stability. A facile synthesis route is developed of 2D nickel oxide decorated functionalized graphene nanosheets (2D-NiO-f:GNSs) hybrids and 3D nitrogen doped bamboo-shaped carbon nanotubes (NCNTs) vertically standing on the functionalized graphene nanosheets (3D-NCNT@f:GNSs) by using a thermal decomposition method. The chemical reduction and morphology-dependent electrochemical response are investigated. The enhanced specific capacitance of 3D-NCNT@f:GNSs as compared to that of 2D-NiO-f:GNSs suggests the synergistic effects and indicates the importance of energy storage and superior long-term cycling performance that are achieved. This 3D-NCNT@f:GNSs hybrid shows a remarkable cycling stability with a maximum power density of 12.32 kW kg-1 and maximum energy density of 109.13 Wh kg-1 due to the good connection of NCNT and f:GNSs. This unique 3D nano network architecture enables the availability of large surface areas of NCNT, thus endowing the nanohybrids with high specific capacitance and excellent reusability. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.